2018
DOI: 10.1017/s0007114518001563
|View full text |Cite
|
Sign up to set email alerts
|

Killed Bifidobacterium longum enhanced stress tolerance and prolonged life span of Caenorhabditis elegans via DAF-16

Abstract: Probiotics are bacteria among the intestinal flora that are beneficial for human health. Bifidobacterium longum (BL) is a prototypical probiotic that is widely used in yogurt making, supplements and others. Although various physiological effects of BL have been reported, those associated with longevity and anti-ageing still remain elusive. Here we aimed to elucidate the physiological effects of killed BL (BR-108) on stress tolerance and longevity of Caenorhabditis elegans and their mechanisms. Worms fed killed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 34 publications
5
31
1
1
Order By: Relevance
“…Moreover, aging worms fed with only killed B. longum displayed longer life span than those fed E. coli alone. This study revealed that killed B. longum effects in C. elegans were mediated by DAF-16 nuclear localization leading to the overexpression of DAF-16 target genes (99). These findings are in contradiction with previous observations with different Bifidobacterium and Lactobacillus strains, which showed the role for SKN-1 independently of DAF-16 (99).…”
Section: Positive and Negative Effects Of Probiotics On The Worm Lifecontrasting
confidence: 97%
“…Moreover, aging worms fed with only killed B. longum displayed longer life span than those fed E. coli alone. This study revealed that killed B. longum effects in C. elegans were mediated by DAF-16 nuclear localization leading to the overexpression of DAF-16 target genes (99). These findings are in contradiction with previous observations with different Bifidobacterium and Lactobacillus strains, which showed the role for SKN-1 independently of DAF-16 (99).…”
Section: Positive and Negative Effects Of Probiotics On The Worm Lifecontrasting
confidence: 97%
“…Bifidobacterium is an important intestinal probiotic [48,49]. The recent study indicated that Bifidobacterium can significantly increase the longevity of Caenorhabditis elegans [50,51]. The present study showed for the first time that Bifidobacterium BB-12 can considerably delay J774A.1 macrophage aging.…”
supporting
confidence: 52%
“…In addition, C. elegans has a short lifespan that allows many assays to be conducted in a limited period of time. Many studies have already been conducted to evaluate the effect of functional dietary components on aging and stress tolerance in C. elegans [18][19][20]; thus, it is a very suitable model to use to conduct preliminary assessments of physiological active compounds, and thereby provide valuable and relevant data to support subsequent studies in higher order animals.…”
Section: Introductionmentioning
confidence: 99%